Tantangan dan Peluang Implementasi Praktik Kerja Lapangan Mahasiswa Ekonomi Syariah: Studi Kasus di STAI Al-Ittihad Cianjur - Dudang Abdul Karim; Sarah Robiatul Adawiyah; Susi Fitria (Jurnal Pendidikan Islam dan Manajemen Ekonomi, 2024)
The implementation of Praktik Kerja Lapangan (PKL) is an integral part of higher education, including at Al-Ittihad Islamic College (STAI) in Cianjur, which offers Sharia Economics programs. However, the implementation of PKL often faces several challenges that affect the quality of students' learning experiences. Literature review highlights the need for enhanced cooperation between educational institutions and the industrial sector, as well as the necessity for better guidance for students during PKL. This research adopts a qualitative approach by interviewing students and Sharia economics faculty at STAI Al-Ittihad Cianjur. The findings indicate that students encounter difficulties in finding suitable PKL placements and perceive a lack of guidance from PKL supervisors. Additionally, it is identified that students tend to feel hesitant to ask questions to supervisors. The implications of these findings underscore the need for improved coordination between educational institutions and industry, training for PKL supervisors, and efforts to create a supportive environment for students. The conclusion of this research emphasizes the importance of addressing these challenges to enhance the quality of Sharia economics education at STAI Al-Ittihad Cianjur.